BANDUNG, THE NON-ALIGNED AND THE MIDIA: THE ROLE OF THE JOURNAL “THIRD WORLD” IN SOUTH-SOUTH DIALOGUE - Bissio, Beatriz (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
The paper traces the history of the Third World journal since its ascension until the closure, analyzing the historical period, the Non-Aligned Movement, including its New International Economic Order and New World Information and Communication Order proposes, and the political conditions that caused the journal’s extinction.